2020
DOI: 10.1111/apt.16172
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus RNA decline without concomitant viral antigen decrease is associated with a low probability of sustained response and hepatitis B surface antigen loss

Abstract: SummaryBackgroundSerum hepatitis B virus (HBV) RNA may reflect intrahepatic HBV replication. Novel anti‐viral drugs have shown potent HBV RNA decline without concomitant hepatitis B surface antigen (HBsAg) decrease. How this relates to off‐treatment response is yet unclear.AimTo study the degree of on‐treatment viral antigen decline among patients with pronounced HBV RNA decrease in relation to off‐treatment sustained response and HBsAg loss.MethodsHBV RNA, HBsAg and hepatitis B core‐related antigen (HBcrAg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Although existing studies have shown the ability of HBsAg levels at EOT to reasonably predict HBsAg loss after cessation (4,(28)(29)(30), it is unable to estimate the probability that a patient will not experience exacerbation and decompensation of hepatitis B. Other studies have shown that detectable levels of hepatitis B core-related antigen (HBcrAg) and HBV RNA at EOT can predict an unfavorable outcome such as relapses; however, the assays lack sensitivity, and the undetectability of these markers is not a strong predictor of HBsAg loss (31)(32)(33)(34)(35). Nevertheless, a recent study by Sonneveld et al (28) showed that quantification of HBcrAg at EOT may be useful in predicting off-therapy HBsAg loss.…”
Section: Livermentioning
confidence: 99%
“…Although existing studies have shown the ability of HBsAg levels at EOT to reasonably predict HBsAg loss after cessation (4,(28)(29)(30), it is unable to estimate the probability that a patient will not experience exacerbation and decompensation of hepatitis B. Other studies have shown that detectable levels of hepatitis B core-related antigen (HBcrAg) and HBV RNA at EOT can predict an unfavorable outcome such as relapses; however, the assays lack sensitivity, and the undetectability of these markers is not a strong predictor of HBsAg loss (31)(32)(33)(34)(35). Nevertheless, a recent study by Sonneveld et al (28) showed that quantification of HBcrAg at EOT may be useful in predicting off-therapy HBsAg loss.…”
Section: Livermentioning
confidence: 99%
“…Thus, their use in combination with on-treatment predictors, such as HBsAg, HBcrAg or HBV-RNA, is under investigation to develop more personalized treatment scores. According to recent reports, an early serum HBV-RNA decline appears to correlate with response to Peg-IFN-α treatment, however only the combined kinetics of viral nucleic acids (HBV-DNA and HBV-RNA) and antigens (HBsAg and HBcrAg) identifies with higher accuracy the patients who achieve a functional cure [43,44].…”
Section: Interferon Treatment Tailoringmentioning
confidence: 99%